Effects of 1,25-Dihydroxyvitamin D3 and 25-Hydroxyvitamin D3 on PBMCs From Dairy Cattle Naturally Infected With Mycobacterium avium subsp. paratuberculosis - Wherry, Taylor L. T.; Mooyottu, Shankumar; Stabel, Judith R. (Frontiers in Veterinary Science, 2022)
The role of vitamin D3 in modulating immune responses has been well established for over two decades; however, its specific functions have not been extensively detailed in cattle, particularly cattle in different stages of infection with Mycobacterium avium subspecies paratuberculosis (MAP). Consistent with previous work in our lab, the present study showed that infected cattle in the clinical stage of disease have reduced serum 25-hydroxyvitamin D3 [25(OH)D3]. Additionally, effects of vitamin D3 on peripheral blood mononuclear cells (PBMCs) from naturally infected dairy cattle in subclinical (n=8) or clinical (n=8) stages of infection were compared to noninfected control cows (n=8). Briefly, PBMCs were isolated and cultured in vitro with 4 ng/ml 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] or 100 ng/ml 25(OH)D3. Treatment with 1,25(OH)2D3 resulted in decreased secretion for some pro-inflammatory cytokines in clinical animals, including IL-1, IL-6, and IFN-. Similar responses for IL-1 and IL-6 were noted with the addition of 25(OH)D3. Additionally, pro-inflammatory cytokine gene expression tended to be upregulated in PBMCs from clinical animals after treatment with 1,25(OH)2D3. In contrast, PBMCs from clinical animals treated with 25(OH)D3 showed downregulation of pro-inflammatory cytokine gene expression, although only significant for IL1B. Following 25(OH)D3 treatment, clinical animals showed significant reduction in CD4+CD25+ T cells. CYP27B1 gene expression was notably decreased in clinical and control animals following 25(OH)D3 treatment but increased in subclinical cows. 1,25(OH)2D3 treatment reduced CYP24A1 gene expression in all groups, while 25(OH)D3 treatment only significantly reduced expression for control cows. Lastly, serum 25(OH)D3 levels were significantly lower in clinical animals. Taken together, these data show vitamin D3 modulates cytokine signaling in cattle at different stages of MAP infection and, therefore, may have implications on disease progression